SARS-CoV-2 and Risk to Food Safety - Anelich, Lucia E. C. M.; Lues, Ryk; Farber, Jeffrey M.; Parreira, Valeria R. (Frontiers in Nutrition, 2020)
The COVID-19 pandemic has brought about a consideration of our understanding of transmission of the causal agent, SARS-CoV-2 to humans and its potential effect on food safety and food security. The main routes of transmission are reported to be person-to-person, by respiratory droplets and to a lesser degree, by fomites. Concerns have been raised on the possibility of transmission via food and food packaging and whether the virus poses a risk to food safety. The current contribution provides an exposé of updated literature and reports applicable to various components of food safety and its linkage to the SARS-CoV-2 virus. The article focuses on SARS-CoV-2 survival in food, on food contact materials and food packaging, and its categorization as a foodborne vs. respiratory virus, the possibility of fecal-oral transmission and the likelihood of infection via the gastro-intestinal system. The survival and inactivation of SARS-CoV-2 in food through thermal and non-thermal inactivation methods as well as the survival and inactivation on inanimate surfaces and effective disinfection of food contact surfaces, are discussed. Ultimately, the article endeavors to add to the body of knowledge pertaining to the role of SARS-CoV-2 in food safety and thereby contribute to an agile and robust fraternity that is equipped to absorb and weather the ongoing effects of the pandemic on the food sector.